The Power of Survey Design : a User's Guide for Managing Surveys, Interpreting Results, and Influencing Respondents. - Iarossi, Giuseppe (World Bank e-Library., 2006)
"Written both for those who manage surveys and those who use their results, The Power of Survey Design not only reveals the multitude of survey design factors that play subtle but crucial roles in the accuracy of survey data and therefore can taint their interpretation, but also offers a guide to the steps involved in administering a survey and convincing potential respondents to participate. Finally, a chapter on data cleaning offers a unique method for improving the accuracy of data after the survey's completion."--Jacket.